Bringing back ecological flows: migratory fish, hydropower and legal maladaptivity in the governance of Finnish rivers. Issue 3 (3rd April 2019) - Soininen, Niko; Belinskij, Antti; Vainikka, Anssi; Huuskonen, Hannu
ABSTRACT: Historically, Finnish rivers supported vital populations of migratory salmonids. Presently, these species are more or less endangered due to extensive damming and hydropower production. In this article, we study the main legal and scientific drivers for re-evaluating some of the existing hydropower operations in Finland. We argue that there is a need for re-evaluation on the basis of legal obligations stemming largely from EU law and new scientific knowledge. Theoretically, our setting opens up a classical adaptive governance problem in how to address laws and past decisions that are based on outdated assumptions about the functioning of social-ecological systems.